Does commission remuneration affect the investor's outcome? Experience from Central Europe. Issue 4 (11th November 2019) - Šindelář, Jiří; Budinský, Petr
Abstract : Purpose: This paper aims to deal with the conflict of interest in the area of investment advice, rewarded through the commission mechanism. Using a substantial data set on sales of independent agents, the authors have examined the relationship between the amount of commission paid to the agent and the subsequent performance of the client's portfolio (annualised five-year returns, volatility and total expenses ratio). Design/methodology/approach: The main working method consisted of linear model with mixed effects. Processing total amount of 2, 066 advised sales from, the authors were able to examine not only the general level of aforementioned relationship but also the effect of different organisational environments, ranging from multi-level marketing (MLM), pool to flat structures. Findings: Contrary to general expectations, the authors have found that investment advisers do recommend products with generally higher costs and volatility, but in the MLM networks, they are at the same time able to generate significantly higher returns on recommended funds. Research limitations/implications: Due to the setting of this study, the authors were only able to cover the vital period of 2007-2018, mostly the "good times" in the region's economy. Such limitation represents guideline for further longitudinal research, which will be followed in the next analytical steps. Practical implications: The results are of interest both to policymakers and final consumers. The first group can better adjust rules in the inducements and advice area, to stimulate shift in different organisational environments. Clients, on the other hand, receive additional guidance on which types of companies generally offer the most beneficial advice. Originality/value: Although research on advice and conflict of interest is prevalent, the meta-analysis shows that only few authors were able to quantitatively disseminate the relationship between remuneration of advisor and subsequent utility of the client. The findings are unique in this regard, bringing statistically conclusive results from region of Central Europe, where advice represents one of the principal distribution channels.